PENGARUH TINGKAT PENDIDIKAN, PDRB, DAN ANGKA PARTISIPASI SEKOLAH TERHADAP INDEKS PEMBANGUNAN MANUSIA (IPM) PADA 6 PROVINSI DI PULAU JAWA - nurwidi, eka; Prihayatni, Enfila (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2023)
This study aims to analyze the impact of education level, GRDP, and school enrollment rates on the Human Development Index (IPM) in six provinces on the island of Java. Secondary data for two years were used in this study, covering the provinces of DKI Jakarta, West Java, Central Java, DIY, East Java and Banten, which were obtained from BPS. The technique in this study is the method of panel data regression analysis. The research findings reveal that simultaneously, education level, GRDP, and school enrollment rates have no significant effect on the Human Development Index in Java. Partially, education level, GRDP, and school enrollment rates also do not have a large or significant impact on the Human Development Index in Java.